Air pollution and meteorological conditions during gestation and type 1 diabetes in offspring. (September 2021) - Taha-Khalde, Alaa; Haim, Alon; Karakis, Isabella; Shashar, Sagi; Biederko, Ron; Shtein, Alexandra; Hershkovitz, Eli; Novack, Lena
Highlights: Exposure to ozone and solar radiation during gestation are both positively associated with type 1 diabetes in offspring. Exposure to SO2 one year prior to the disease onset is positively associated with type 1 diabetes. More scientific evidence needs to accumulate to support the study findings. Abstract: Background: Growing evidence indicates that air pollution is capable of disrupting the immune system and therefore, might be associated with an onset of Type 1 diabetes (T1D). Objectives: We explored possible links of T1D with ambient exposures in the population of southern Israel, characterized by hot and dry climate and frequent dust storms. Methods: We conducted a matched nested case-control study where exposure to environmental pollutants during gestation in T1D cases was compared to that of healthy children. Up to 10 controls were matched to every case by age, gender and ethnicity, in all 362 cases and 3512 controls. Measurements of pollutants' concentrations, nitrogen dioxide (NO2 ), sulphur dioxide (SO2 ), ozone (O3 ) and particulate matter of size less than 10 and 2.5 μm in diameter (PM10 and PM2.5 ), as well as the mean daily measurements of meteorological conditions were obtained from the local monitoring stations. The association between T1D and pollution, solar radiation (SR), temperature and relative humidity was adjusted for socioeconomic status, temperature, maternal age and pre-gestational maternal DM, using conditional logistic regression. The environmental exposures were presented as indicators of quartiles averaged over whole pregnancy and by trimesters. Results: Exposure to ozone and solar radiation during gestation were both associated with the T1D in offspring, although at borderline significance. Compared to the lowest quartile, the odds ratio (OR) for exposure to 3rd and 4th quartile of O3 was equal 1.61 (95%CI: 0.95; 2.73) and 1.45 (95%CI: 0.83; 2.53), respectively. Likewise, the ORs for exposure to SR were equal 1.83 (95%CI: 0.92; 3.64), 2.54 (95%CI: 1.21; 5.29) and 2.06 (95%CI: 0.95; 4.45) for to 2nd, 3rd and 4th quartiles, respectively. Exposure to SO2 followed a dose-response pattern, but was not statistically significant. Other environmental factors were not independently related to T1D. Analysis of exposures one year prior to the disease onset indicated a positive association between T1D and SR. Conclusions: We showed that exposure to high ozone levels and solar radiation during gestation might be related to the T1D. More scientific evidence needs to accumulate to support the study findings.